A Sociocultural Framework to Analyse M-Learning Options for Early Childhood Development (ECD) Practitioner Training - Oosthuizen, Susanna; Roberts, Nicky (LINK Centre, University of the Witwatersrand (Wits), Johannesburg, 2021)
This article, a contribution to m-learning (mobile learning) research, centres on the motivation for, and development of, a suitable framework to analyse m-learning options for early childhood development (ECD) practitioners. Grounded in a sociocultural learning perspective, the framework was developed as part of a larger study into the feasibility of m-learning for ECD practitioners in the Penreach professional development programme in Mpumalanga Province, South Africa. Analysis of existing frameworks enabled the development of a new, modified framework to suit the Penreach context. Here we unpack the framework and explain its development. The new, modified framework aims to assist researchers, developers, and implementers by prompting consideration of five sociocultural learning features associated with m-learning in ECD, namely: device access, data affordability, authenticity, collaboration, and personalisation.
Keywords: m-learning, mobile learning, early childhood development (ECD), professional development, training, sociocultural learning